Focus on musculoskeletal health in women with bleeding disorders - Dougall Alison; Frenzel Laurent (The Journal of Haemophilia Practice, 2022)
Maintaining good musculoskeletal health, including good oral health, is as important for women with bleeding disorders (WBD) as it is for men. Many people with bleeding disorders ignore bleeding from their gums, believing it to be part of their condition. However, it may be a sign of periodontal disease, which left untreated can lead to accelerated tooth loss and infection, adversely affecting overall health. A good diet and access to good dental care from childhood are important to maintaining good oral health in WBD. Joint bleeding and degeneration are not limited to people with more severe forms of haemophilia; joint-related diagnoses have been shown to be twice as common among haemophilia carriers and women with mild haemophilia than in the general population. Women with type 3 von Willebrand disease experience comparable joint outcomes to younger intensively treated patients with severe haemophilia. Neither gum nor joint bleeds should ever be considered normal, as both can be treated to avoid progressive disease. Dental and joint specialists and physiotherapists should work closely with haemophilia teams to ensure optimal care for long-term preservation of musculoskeletal health.